The Long-term Performance of PE-backed Buyouts in the UK: Divisional Buyouts and PE Syndication - Cheng, Libin (2012)
Abstract The agency and strategic entrepreneurship theories on buyouts have be reviewed in this paper, which has provided complementary insights into three research questions relating to the long-term post-buyout performance of PE-backed buyouts. First, are there any differences in the long-term performance between divisional buyouts and other types of private buyouts? Second, are there any differences in the long-term performance between PE-syndicate-backed and individual-PE-backed buyouts? Third, do syndicated PE firms impact differently on the long-term performance of divisional buyouts than for other private buyouts? These questions have been examined by analyzing a hand-collected sample data of 122 completed PE-backed buyouts in the UK between 2000 and 2006. The OLS regressions have been run to analyze these questions, and the results have provided strong supports that: divisional buyouts perform better in sales and employment growth than other private buyouts; PE-syndicate-backed firms have higher employment growth than those backed by individual PE firms; PE syndication and divisional buyouts may have more positive impacts on the enhancement of efficiency of buyout firms. This study then strongly supports to the view of value creation on the post-buyout performance.